Maqasid al-Shariah-based strategies for enhancing digital adoption among B40 Muslim entrepreneurs - Busari, Saheed Abdullahi; Abd. Rokis, Rohaiza; Md. Sawari, Mohd Fuad; Mohamadali, Noor Azizah; Amanullah, Muhammad (IIUM Press, 2025)
In Malaysia’s pursuit of a digital economy, many B40 Muslim entrepreneurs remain excluded due to socioeconomic constraints and a lack of alignment between digital initiatives and Islamic ethical values. This study investigates how Maqasid al-Shariah principles can be strategically applied to enhance digital adoption among this underserved group. The objective is to develop a values-driven framework that integrates Islamic ethical priorities into digital inclusion strategies. A qualitative methodology was employed, combining library research for conceptual and theoretical grounding with focus group discussions (FGDs) involving Islamic scholars, digital economy practitioners, policymakers, and B40 Muslim entrepreneurs to capture diverse perspectives and enhance validity. The findings reveal that the fundamental objectives of Maqasid al-Shariah, especially protection of wealth (Hifz al-Mal) and dignity (Hifz al-‘Ird), provide a relevant foundation for fostering ethical and sustainable digital adoption. Sub-themes include incentivizing compliance, integrating Islamic values into digital tools, promoting Shariah-compliant financial products, and leveraging religious institutions for digital education. This study offers practical and theoretical contributions by proposing a Maqasid al-Shariah-based digital inclusion framework for Muslim entrepreneurs in the B40 segment. Its implications extend to policymakers, Islamic fintech developers, and educators seeking to promote equitable and ethically grounded digital participation in Muslim-majority societies.